Clinical and epidemiological characteristics of registered childhood tuberculosis cases in the North-Western Region of Russia when introducing a tuberculosis diagnosis complex using diaskintest and multislice spiral computed tomography - I. F. Dovgalyuk; N. V. Korneva; A. A. Starshinova; Yu. E. Ovchinnikova; S. M. Ananyev (Туберкулез и болезни лёгких)
The paper analyzes changes in the pattern of clinical forms of registered tuberculosis cases, in the proportion of detected complications and phases of the specific process in children in 2007 to 2012. The findings were compared with registered morbidity rates and changes in the set of performed examinations [introduction of diaskintest (DST) and computed tomography (CT)] in 5 areas of the North-Western Region of the Russian Federation. There was a rise in the notified number of children with tuberculosis in some areas and a decline in the others, which is due to different frequencies to use DST and CT in the diagnostic complex. The wide introduction of CT may be a cause of more frequent detection of the specific process in the phase of involution and calcification because standard radiographic techniques used in the early stages of the specific process fail to diagnose these changes. The findings suggest the untimely detection of the disease and necessitate an improvement in the screening of children for the early manifestations of tuberculosis infection.